2004
DOI: 10.1055/s-2004-831197
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Activation of Zinc: Application of the Blaise Reaction to an Expedient Synthesis of a Statin Intermediate

Abstract: Efficient and practical in situ zinc activation was accomplished by treatment with catalytic amount of an organic acid. The protocol was applied successfully to the Blaise reaction of various nitriles. Noteworthy is the excellent Blaise transformation of (S)-4-chloro-3-trimethylsilyloxybutyronitrile (2b) into tert-butyl (S)-6-chloro-5-hydroxy-3-oxohexanoate (1), a key intermediate for the preparation of HMG-CoA reductase inhibitors (statins).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Homologation to the β-ketoester 1 was accomplished via Blaise reaction of the nitrile 4 with BrCH 2 CO 2 Et. We found that reproducibly high yields in this reaction could be achieved using activated Zn 0 metal and in situ activation with a catalytic amount of TFA . Diazo transfer using MsN 3 then provided the requisite α-diazo-β-ketoester 5 for C−H functionalization.…”
Section: Resultsmentioning
confidence: 91%
“…Homologation to the β-ketoester 1 was accomplished via Blaise reaction of the nitrile 4 with BrCH 2 CO 2 Et. We found that reproducibly high yields in this reaction could be achieved using activated Zn 0 metal and in situ activation with a catalytic amount of TFA . Diazo transfer using MsN 3 then provided the requisite α-diazo-β-ketoester 5 for C−H functionalization.…”
Section: Resultsmentioning
confidence: 91%
“…The pyridines 2-aminopyridine, 1 , 2-amino-4-hydroxypyridine, 2 , 2-amino-3-hydroxypyridine, 3 , and the β-keto esters ethyl benzoylacetate, 4 , ethyl 4-methoxybenzoylacetate, 5 , and ethyl 3,4-dimethoxybenzoylacetate, 6 , used to obtain the target inhibitors, were from Aldrich and Fluka. The following compounds were prepared in accordance with a reported procedure: ethyl 3-oxo-4-phenylbutanoate, 7 , ethyl 4-(4-methoxyphenyl)-3-oxobutanoate, 8 , and ethyl 4-(3,4-dimethoxyphenyl)-3-oxobutanoate, 9 .…”
Section: Methodsmentioning
confidence: 99%
“…Formation of ether (R)-19 from ether nitrile 24 was achieved by a modified Blaise reaction (81 %). [20] The procedure benefited from simple in situ activation of zinc dust with MeSO 3 H and required only 2 equiv of ethyl bromoacetate, which minimised and avoided the formation of ethyl acetoacetate and diethyl butandioate byproducts, respectively. Diazo transfer [11] with ether (R)-19 gave diazo ether (R)-10 in 92 % yield.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%